The Role of Organizational Culture in Improving Employee Performance through Human Resource Development - Digor Mufti; Rizka Cintya Edwar; Akmal Ridwan; Samsinar (LP2M IAIN Palopo, 2025)
The impact of organizational culture on employee performance is crucial in enhancing productivity and work environment within companies. This study explores the influence of organizational culture on employee performance, with human resource development acting as a mediating factor. The research employs a quantitative approach using Partial Least Squares (PLS) analysis, based on survey data collected from 32 employees at CV. Pangan Makmur Irja Sorong. The findings reveal that organizational culture has a positive influence on both employee performance and human resource development. However, despite the positive influence of human resource development on employee performance, this effect was found to be statistically insignificant. Additionally, human resource development was not a significant mediator between organizational culture and employee performance. This research contributes to existing literature by providing insights into the mediating role of human resource development in the context of organizational culture and employee performance in SMEs in Sorong. The practical implication of this study suggests that managers should focus on reinforcing organizational culture and aligning human resource development programs with organizational goals to improve employee performance. Targeted HR development initiatives can be a key factor in supporting overall business objectives and improving company performance.